Evaluasi Implementasi Pembelajaran Saintifik Kurikulum 2013 Pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII Di SMP Negeri 2 Merapi Barat Kabupaten Lahat - Istapra, Eva; Hadiwinarto, Hadiwinarto (JPT : Jurnal Pendidikan Tematik, 2020)
The implementation of the 2013 curriculum scientific learning is the application of a student-oriented or student-centered learning approach (Student centered approach). Learning with a scientific approach makes students construct knowledge for themselves. Learning in the 2013 curriculum uses a scientific approach or a scientific process-based approach and the scientific approach also uses several strategies such as contextual learning. The purpose of this study is to determine the implementation of scientific learning curriculum 2013 in Islamic religious education subjects, especially to find out the implementation of Islamic religious education teachers in implementing scientific learning curriculum 2013 in Islamic religious education subjects class VIII at SMP Negeri 2 Merapi Barat regency. Lahat. This type of research is field research (field research) where the research will go directly to the field to conduct research using qualitative descriptive, data sources, primary data and secondary data, using data collection techniques which include observation, interviews, documentation and data analysis techniques using descriptive namely by describing the results of the data obtained in the research field. The results of this research, namely, the implementation of scientific learning curriculum 2013 in Islamic religious education subjects class VIII at SMP Negeri 2 Merapi Barat Lahat Regency has been running according to the theory put forward by Sudarwan in chapter II and covers three aspects, namely knowing, understanding, and practicing.